Bacteriophage XP-12-induced exonuclease which preferentially hydrolyzes nicked DNA. - Farber, M B (1980)
An exonuclease has been partially purified from XP-12-infected Xanthomonas oryzae which is not found in uninfected X. oryzae. Although both the phage-induced exonuclease and the major host exonucleolytic DNase released 5'-mononucleotides, these enzymes differed in their chromatographic behavior, pH optimum, salt inhibition, and heat sensitivity. These two exonucleases preferred different substrates. Nicked native DNA was the best substrate for the phage-induced enzyme, whereas denatured DNA was the best substrate for the host enzyme. Also, the host enzyme had a significant preference for denatured or nicked, normal cytosine-containing DNA (e.g., X. oryzae or T7 DNA) over similarly denatured or nicked 5-methylcytosine-rich DNA (namely, XP-12DNA), whereas the phage-induced enzyme hydrolyzed both types of DNA equally well.